2021
DOI: 10.7150/thno.53755
|View full text |Cite
|
Sign up to set email alerts
|

Highly specific and label-free histological identification of microcrystals in fresh human gout tissues with stimulated Raman scattering

Abstract: Gout is a common metabolic disease with growing burden, caused by monosodium urate (MSU) microcrystal deposition. In situ and chemical-specific histological identification of MSU is crucial in the diagnosis and management of gout, yet it remains inaccessible for current histological methods. Methods: Stimulated Raman scattering (SRS) microscopy was utilized to image MSU based on its fingerprint Raman spectra. We first tested SRS for the diagnosis capability of gout and the differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Details of the SRS microscope setup are provided in our previous work 45 46. Two laser beams of different frequencies, ω p and ω s , coincide on the sample; the difference in matches with a particular molecular vibrational frequency Ω, inducing amplification of Raman signals by a factor of ~10 5 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the SRS microscope setup are provided in our previous work 45 46. Two laser beams of different frequencies, ω p and ω s , coincide on the sample; the difference in matches with a particular molecular vibrational frequency Ω, inducing amplification of Raman signals by a factor of ~10 5 .…”
Section: Methodsmentioning
confidence: 99%
“…The optical power of the pump and Stokes beams at the sample were kept around 80 mW and 160 mW, respectively. SRS was able to specifically and quantitatively evaluate MSU crystals and surrounding tissue background in human synovial fluids or tophi specimens 45…”
Section: Methodsmentioning
confidence: 99%
“…The metabolic index is an indicator of cellular metabolic activity and is defined as the ratio of the integrated spectral intensity of the C-D (2040-2300 cm −1 ) band over the sum of the C-D and C-H bands (2800-3100 cm −1 ). The Raman spectra of biological samples reflect their fingerprints [22,23]; previous studies in which bacteria were cultured in medium containing deuterium suggested that the Raman band at 2170 cm −1 was due to the carbon-deuterium (C-D) bond in the newly synthesized lipids and protein [16]. The generation of biological building blocks containing a C-D bond was due to the incorporation of deuterium from D 2 O into biomolecules via NADPH regeneration by metabolically active cells; NADPH regeneration is an intracellular anabolic biochemical process (illustrated in Figure S3).…”
Section: Influence Of Deuterium Concentration and Incubating Duration On Deuterium Labelingmentioning
confidence: 99%
“…Stimulated Raman scattering (SRS) offers a gain of Raman scattering efficiency by 3–5 orders of magnitude, enabling high-speed chemical imaging. SRS microscopy hence overcomes the speed limit of Raman imaging while retaining the spectral identities for molecule-specific detection. Moreover, SRS microscopy could provide tissue histology similar to traditional H&E staining based on the chemical contrast of intrinsic biomolecules such as lipids, proteins, and DNA. Compared with frozen H&E staining, SRS microscopy has the advantages of imaging fresh, unprocessed tissues to achieve near real-time tissue histology in the operating room. In addition to lipid and protein contents, collagen fibers are known to correlate with cancer fibrosis and tumor cell intravasation , and may play a protective role in controlling pancreatic cancer progression . Hence, it is necessary to include collagen fiber-specific detection with second harmonic generation (SHG) during SRS imaging. Up to now, SRS/SHG microscopy has shown potential in the diagnosis and evaluation of many types of human tumor tissues, including laryngeal carcinoma, brain tumor, and breast cancer. ,, However, the possibility of use of SRS microscopy for human pancreatic tumor imaging and intraoperative guidance has never been investigated.…”
Section: Introductionmentioning
confidence: 99%